Metal-Organic Frameworks-Based Sensors for the Detection of Toxins in Food: A Critical Mini-Review on the Applications and Mechanisms - Xuan, Xiaoxu; Wang, Mengjie; Manickam, Sivakumar; Boczkaj, Grzegorz; Yoon, Joon Yong; Sun, Xun (Frontiers in Bioengineering and Biotechnology, 2022)
Using scientific technologies to detect toxins in food is significant to prevent food safety problems and protect people’s health. Recently, the rise of sensors has made rapid, efficient, and safe detection of food toxins possible. One of the key factors impacting the sensor's performance is the nanomaterials employed. Metal-organic frameworks (MOFs), with high specific surface area, tunable composition, porous structure, and flexible properties, have aroused the interest of researchers. The applications of MOFs in detecting food toxins have seen remarkable success in the past few years. In this critical mini-review, the impact of various synthesis methods on MOFs’ properties is first presented. Then, the applications and mechanisms of MOFs-based sensors in detecting various toxins are summarized and analyzed. Finally, future perspectives, potential opportunities, and challenges in this field are discussed.